Phytosanitary risk associated with illegal importation of pest-infested commodities to the South African agricultural sector - Phumudzo P. Tshikhudo; Livhuwani R. Nnzeru; Maanda Rambauli; Rudzani A. Makhado; Fhathuwani N. Mudau (South African Journal of Science, 2021)
We evaluated the phytosanitary risk associated with illegal importation of pest-infested plant commodities into South Africa. Samples were collected from different South African ports of entry over 8 years (2011 to 2019) and data were analysed descriptively using Statistical Software Package. Pests were frequently detected on commodity species such as Citrus (18.31%), Zea mays (13.22%), Phaseolus vulgaris (12.88%), Musa spp. (9.15%) and Fragaria ananassa (5.08%). The highest number of pests intercepted occurred on fresh fruits (44.06%), followed by grains (26.44%) and vegetables (14.23%). The most intercepted organisms were Callosobruchus rhodesianus (7.79%), Dysmicoccus brevipes (7.11%), Callosobruchus maculates (6.10%) and Phyllosticta citricarpa (4.74%). The majority of intercepted organisms were non-quarantine organisms (70.50%), followed by pests of unknown status (17.28%), quarantine pests (10.84%) and potential quarantine pests (1.35%). Phyllosticta citricarpa, Bactrocera dorsalis, Spodoptera frugiperda and Prostephanus truncatus were the only quarantine pests intercepted in terms of South African regulatory status. The interception was mainly from southern African countries, particularly Mozambique, Zimbabwe and Eswatini. The findings present the level of phytosanitary risk associated with illegal importation and/or non-compliance in regard to plants and plant commodities from different countries through South African ports of entry. Crop production, biodiversity, food security, existing export markets, and access to new export markets could be threatened as importing countries may impose stringent phytosanitary measures to limit the chances of introduction and establishment of quarantine pests into their territories.